Pre‐eclampsia‐like syndrome induced by severe COVID‐19: a prospective observational study. (21st June 2020) - Mendoza, M; Garcia‐Ruiz, I; Maiz, N; Rodo, C; Garcia‐Manau, P; Serrano, B; Lopez‐Martinez, RM; Balcells, J; Fernandez‐Hidalgo, N; Carreras, E; Suy, A
Abstract : Objectives: To investigate the incidence of clinical, ultrasonographic and biochemical findings related to pre‐eclampsia (PE) in pregnancies with COVID‐19, and to assess their accuracy to differentiate between PE and the PE‐like features associated with COVID‐19. Design: A prospective, observational study. Setting: Tertiary referral hospital. Participants: Singleton pregnancies with COVID‐19 at >20 +0  weeks. Methods: Forty‐two consecutive pregnancies were recruited and classified into two groups: severe and non‐severe COVID‐19, according to the occurrence of severe pneumonia. Uterine artery pulsatility index (UtAPI) and angiogenic factors (soluble fms‐like tyrosine kinase‐1/placental growth factor [sFlt‐1/PlGF]) were assessed in women with suspected PE. Main outcome measures: Incidence of signs and symptoms related to PE, such as hypertension, proteinuria, thrombocytopenia, elevated liver enzymes, abnormal UtAPI and increased sFlt‐1/PlGF. Results: Thirty‐four cases were classified as non‐severe and 8 as severe COVID‐19. Five (11.9%) women presented signs and symptoms of PE, all five being among the severe COVID‐19 cases (62.5%). However, abnormal sFlt‐1/PlGF and UtAPI could only be demonstrated in one case. One case remained pregnant after recovery from severe pneumonia and had a spontaneous resolution of the PE‐like syndrome. Conclusions: Pregnant women with severe COVID‐19 can develop a PE‐like syndrome that might be distinguished from actual PE by sFlt‐1/PlGF, LDH and UtAPI assessment. Healthcare providers should be aware of its existence and monitor pregnancies with suspected pre‐eclampsia with caution. Tweetable abstract: This study shows that a pre‐eclampsia‐like syndrome could be present in some pregnancies with severe COVID‐19. Tweetable abstract: This study shows that a pre‐eclampsia‐like syndrome could be present in some pregnancies with severe COVID‐19.